Improving Educational Opportunity and Equity through School District Consolidation in Maine - Donis-Keller, Christine; O’Hara-Miklavic, Beth; Fairman, Janet (Maine Policy Review, 2013)
In 2007 Maine passed sweeping school district consolidation legislation mandating a reduction in the number of Maine school districts from 290 to approximately 80. The primary goals of the policy were to improve the educational opportunities for all students in the state; and to reduce costs through increased efficiency in the delivery of education programs and services. Based primarily on interviews with district leaders, this article describes the impacts of Maine’s school district consolidation policy on educational opportunities and equity within 24 regional school districts, one year after their mergers. Findings illustrate the different choices districts made when consolidating their educational programs, the outcomes of these efforts, and the strategies and structures districts used to implement change.
Keywords: Maine; school district consolidation; school district reorganization; educational quality; educational equity